Laser Direct‐Write Sensors on Carbon‐Fiber‐Reinforced Poly‐Ether–Ether–Ketone for Smart Orthopedic Implants - Xingjian Hu; Jincai Huang; Yanzhuo Wei; Haiyan Zhao; Shize Lin; Chuxiong Hu; Ze Wang; Zhe Zhao; Xining Zang (Advanced Science, 2022)
Abstract Mechanically close‐to‐bone carbon‐fiber‐reinforced poly‐ether–ether–ketone (CFR‐PEEK)‐based orthopedic implants are rising to compete with metal implants, due to their X‐ray transparency, superior biocompatibility, and body‐environment stability. While real‐time strain assessment of implants is crucial for the postsurgery study of fracture union and failure of prostheses, integrating precise and durable sensors on orthopedic implants remains a great challenge. Herein, a laser direct‐write technique is presented to pattern conductive features (minimum sheet resistance <1.7 Ω sq–1) on CRF‐PEEK‐based parts, which can act as strain sensors. The as‐fabricated sensors exhibit excellent linearity (R2 = 0.997) over the working range (0–2.5% strain). While rigid silicon‐ or metal‐based sensor chips have to be packaged onto flat surfaces, all‐carbon‐based sensors can be written on the complex curved surfaces of CFR‐PEEK joints using a portable laser mounted on a six‐axis robotic manipulator. A wireless transmission prototype is also demonstrated using a Bluetooth module. Such results will allow a wider space to design sensors (and arrays) for detailed loading progressing monitoring and personalized diagnostic applications.